Information Modelling and Knowledge Bases XIX - Jaakkola, Hannu (IOS Press, 2013)
In the last decades information modelling and knowledge bases have become hot topics not only in academic communities related to information systems and computer science but also in business areas where information technology is applied. The 17th European-Japanese Conference on Information Modelling and Knowledge Bases, EJC 2007, continues the series of events that originally started as a cooperation between Japan and Finland as far back as the late 1980’s. Later (1991) the geographical scope of these conferences expanded to cover all of Europe as well as countries outside Europe other than Japan.